Effects of ruminally-protected lysine supplementation on growing and finishing performance of beef cattle - de Aguiar Veloso, Vanessa (Kansas State University, 2020)
Three experiments were conducted to evaluate impacts of supplementing ruminally-protected lysine (RPL) to growing and finishing cattle. In experiment 1, 448 heifers (287 ± 14.1 kg body weight (BW)) were used to evaluate backgrounding performance of cattle fed RPL (SafeGainTM, H.J. Baker & Bro. LLC., Shelton, CT). Treatments were RPL supplemented at 0, 15, 30, or 45 g/animal daily. Heifers were blocked by BW and randomly allocated to 16 blocks of 4 pens each for a total of 64 pens containing 7 heifers/pen. At the end of the 112-day backgrounding period, a subset of 12 blocks were consolidated, such that 2 pens from each backgrounding treatment were combined into one finishing pen. Cattle were weighed, relocated to finishing pens, and fed a common finishing diet (no supplemental lysine) for 95 days until harvest to evaluate carryover effects of RPL fed during backgrounding. In experiment 2, 384 steers (413 ± 29.2 kg BW) were used to evaluate effects of supplementing RPL (SafeGain, H.J. Baker & Bro.) in conjunction with a β-adrenergic agonist (BAA) on performance and carcass characteristics. Treatments were (2 x 4 factorial) 0, 20, 40, or 60 g/animal daily of RPL in conjunction with BAA during the last 42 days on feed (112 days total finishing period); and two step-up regimens: conventional 21-days without or an accelerated 10-days step-up with an oral dose of Megasphaera elsdenii probiotic (ME; Lactipro®, MS Biotec, Wamego, KS). Steers were blocked by BW and randomly allocated to one of 64 pens with 6 animals/pen. In experiment 3, 448 steers (352 ± 25 kg BW) were used to evaluate impact of ME, alone or in combination with RPL (USA Lysine, Kemin Industries Inc., Des Moines, IA), on performance and carcass characteristics. Steers were blocked by BW and randomly allocated to one of 64 pens (7 steers/pen). Treatments were arranged as a 2 x 2 factorial in a randomized complete block experiment, with treatments consisting of: RPL fed at 0 or 45 g/animal daily; and two step-up regimens as described for Exp. 2. Finishing diets were fed once daily for 144 or 172 days, ad libitum. At the end of all trials, cattle were weighed and harvested at a commercial abattoir, where carcass data were collected. In all studies, pen was the experimental unit, and block was the random effect. Backgrounding performance improved linearly in response to increasing amounts of RPL (P ≦ 0.05) in Exp. 1, and improvements realized during background were retained throughout finishing. In Exp. 2, there were no effects of RPL or ME on daily gain (ADG), dry matter intake (DMI), or gain:feed (P > 0.45); but liver abscess incidence was increased with RPL supplementation (P < 0.05; 28.3, 39.0, 46.9 and 39.4% for cattle fed 0, 20, 40 and 60 g/day of RPL, respectively). An interaction between RPL and ME was observed for hot carcass weight (P = 0.01). Dosing cattle with ME with an accelerated transition period decreased marbling score (P = 0.03) and yielded a lower percentage of carcasses grading Choice (P = 0.03) than those traditionally adapted. No other effects of ME or RPL were observed for carcass characteristics (P > 0.10). In Exp. 3, no interactions between ME and RPL (P > 0.1) were observed. Steers given ME consumed less roughage compared to their counterparts without (P < 0.05), but ADG, DMI, and gain:feed were similar (P > 0.10) among treatments. Administering ME tended to increase percentage of USDA Prime carcasses compared to control (2.7 vs 0.5% respectively; P = 0.06). Feeding RPL did not affect feedlot performance, hot carcass weight, or other carcass traits (P > 0.10) but tended to increase USDA Yield Grade (P < 0.07). Thus, supplementing RPL improved backgrounding performance, but no benefits were observed during feedlot finishing. Additionally, an accelerated step-up program with ME yielded finishing performance comparable to that of traditionally-adapted cattle.
Keywords: Feedlot; Megasphaera elsdenii; Ruminally-protected lysine